2022
DOI: 10.3390/life12050671
|View full text |Cite
|
Sign up to set email alerts
|

Appetite in Palliative Cancer Patients and Its Association with Albumin, CRP and Quality of Life in Men and Women—Cross-Sectional Data from the Palliative D-Study

Abstract: Albumin is an important biochemical marker in palliative cancer care, used for assessment of nutritional status, disease severity and prognosis. Our primary aim was to investigate sex differences in the association between appetite and albumin levels in palliative cancer patients. We also aimed to study associations between appetite and C-reactive protein (CRP), Quality of Life (QoL), pain and fatigue. In the Palliative D-cohort, consisting of 266 men and 264 women, we found a correlation between appetite and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…These observations are consistent with similar studies that have been reported in the literature. 9,44,6264 Yennurajalingam et al 44 used the ESAS patient-reported outcome questionnaire to investigate factors associated with a feeling of wellbeing among 826 advanced lung or non-colonic gastrointestinal cancer patients and observed that patient-reported wellbeing was significantly associated with tiredness. Wilding et al 63 also investigated the associations between cancer-related symptoms, health-related quality of life and poor psychological outcomes in 13,097 prostate cancer patients treated with androgen deprivation therapy (ADT) and reported that clinically significant tiredness was strongly associated with poor wellbeing in patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations are consistent with similar studies that have been reported in the literature. 9,44,6264 Yennurajalingam et al 44 used the ESAS patient-reported outcome questionnaire to investigate factors associated with a feeling of wellbeing among 826 advanced lung or non-colonic gastrointestinal cancer patients and observed that patient-reported wellbeing was significantly associated with tiredness. Wilding et al 63 also investigated the associations between cancer-related symptoms, health-related quality of life and poor psychological outcomes in 13,097 prostate cancer patients treated with androgen deprivation therapy (ADT) and reported that clinically significant tiredness was strongly associated with poor wellbeing in patients.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with other similar studies that have been reported in the literature. 9,23,44,45,6264…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 37 ]. Decision making regarding observation and assessment is vital for administrating effective advanced directives [ 23 , 38 ]. Therefore, assessment of appetite loss by patients and their families is useful for advanced directives and palliative care for unresectable pancreatic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Care level was divided into two groups (dependent: ≥1 and non-dependent: <1) based on the burden on caregivers and families. Appetite loss was assessed based on the Edmonton Symptom Assessment System, and this information was obtained from the review of systems by the nurses at the first visit for each patient [ 23 ].…”
Section: Methodsmentioning
confidence: 99%